PERSEPSI NILAI INFORMASI DAN DAMPAKNYA TERHADAP KUALITAS INFORMASI PADA LINE TODAY NEWS MEDIA PLATFORM - Legiansyah, Geovani; Kurnia, Kurnia (Transpublika Publisher, 2023)
Advances in information technology today make it easier to search and broadcast information content. The Digital Platform has become a media channel that has experienced a significant increase in information dissemination and meeting information needs. Percieved Value can be measured through three main dimensions where the audience has three expectations of value for quality information based on Verbal information, Nonverbal information. This research is a quantitative research with the population understanding the value of satisfaction and quality of information. The research sample was determined using the Lameshow Sample Size. The data were analyzed using Partial Least Square (PLS) with the stages of testing the measurement model through validity and reliability tests and structural model testing to assess the significance of the research hypothesis. Line Today users in Indonesia are still very high, with the majority of respondents being male with a percentage of 56% and female only 44%. For the age of the respondents, the predominant range is between 18 – 24 years with a percentage of 69% and most of them are domiciled in Jabodetabek (80%). The value of the Coefficient of Determination (R2Information) Qualityy 76.2% is explained by the variables Quality of Verbal Information and Quality of Non Verbal Information.